Are mastectomy rates really increasing in the United States? - Habermann, Elizabeth B; Abbott, Andrea; Parsons, Helen M; Virnig, Beth A; Al-Refaie, Waddah B; Tuttle, Todd M (Journal of clinical oncology, 2010)
After the National Institutes of Health Consensus Statement in 1990, breast-conserving surgery (BCS) became more common while mastectomy rates decreased. However, several recently published single-institution studies have reported an increase in mastectomy rates in the past decade. We conducted a population-based study to evaluate national trends in the surgical treatment of breast cancer from 2000 through 2006. Using the Surveillance, Epidemiology, and End Results database, we conducted a retrospective cohort analysis of women undergoing surgical treatment for breast cancer. We evaluated variation in mastectomy rates by demographic and tumor factors and calculated differences in mastectomy rates across time. We utilized logistic regression to identify time trends and patient and tumor factors associated with mastectomy, testing for significance using two-sided methods. We identified 233,754 patients diagnosed with ductal carcinoma in situ or stage I to III unilateral breast cancer from 2000 to 2006. The proportion of women treated with mastectomy decreased from 40.8% in 2000 to 37.0% in 2006 (P < .001). These patterns were maintained across patient and tumor factors. Although the unilateral mastectomy rate decreased during the study period, the contralateral prophylactic mastectomy rate increased. Women were less likely to receive mastectomy over time (odds ratio, 1.18 for 2000 v 2006; 95% CI, 1.14 to 1.23; P < .0001), after adjusting for patient and tumor factors. In contrast to single-institution studies, our population-based analysis found a decrease in unilateral mastectomy rates from 2000 to 2006 in the United States. Variations in referral patterns and patient selection are potential explanations for these differences between single institutions and national trends.